2016
DOI: 10.1074/mcp.m116.062349
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics Evidence for Inheritance of Energy Pathways in Red Blood Cells

Abstract: Each year over 90 million units of blood are transfused worldwide. Our dependence on this blood supply mandates optimized blood management and storage. During storage, red blood cells undergo degenerative processes resulting in altered metabolic characteristics which may make blood less viable for transfusion. However, not all stored blood spoils at the same rate, a difference that has been attributed to variable rates of energy usage and metabolism in red blood cells. Specific metabolite abundances are herita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…The heritability of energy metabolism in RBCs was established in the 1960s. In twin studies, we confirmed the heritability of pre‐ and poststorage RBC ATP concentrations, glutathione metabolism, hemolysis, and activity of the glycolytic pathway . Two heritable pathways affecting RBC storage have emerged: 1) inheritance of higher glycolytic activity correlates with higher ATP during storage and 2) inheritance of higher concentrations of carbonic anhydrase 1 (CA1) correlate with lower ATP during storage.…”
Section: Session 3: Methods For the Detection Of Rbc Processing And Ssupporting
confidence: 58%
See 1 more Smart Citation
“…The heritability of energy metabolism in RBCs was established in the 1960s. In twin studies, we confirmed the heritability of pre‐ and poststorage RBC ATP concentrations, glutathione metabolism, hemolysis, and activity of the glycolytic pathway . Two heritable pathways affecting RBC storage have emerged: 1) inheritance of higher glycolytic activity correlates with higher ATP during storage and 2) inheritance of higher concentrations of carbonic anhydrase 1 (CA1) correlate with lower ATP during storage.…”
Section: Session 3: Methods For the Detection Of Rbc Processing And Ssupporting
confidence: 58%
“…In twin studies, we confirmed the heritability of pre-and poststorage RBC ATP concentrations, glutathione metabolism, hemolysis, and activity of the glycolytic pathway. [28][29][30] Two heritable pathways affecting RBC storage have emerged: 1) inheritance of higher glycolytic activity correlates with higher ATP during storage and 2) inheritance of higher concentrations of carbonic anhydrase 1 (CA1) correlate with lower ATP during storage. CA1 concentrations correlate negatively with pH, suggesting that the effect of CA1 may involve the production of acid, with resulting inhibition of glycolytic enzymes.…”
Section: Systems Biology Of Rbc Storage Lesions-bernhard Palsson Phdmentioning
confidence: 99%
“…In the last 7 years, such large-scale studies as the Recipient Epidemiology and Donor Evaluation Study-III have addressed the issue of biological variability and found that biological variability across donors (i.e., donor ethnicity, gender, and age) affects RBC storability and stress hemolysis ( 18 ). Such observations have been supported by smaller scale laboratory studies in humans ( 19 , 20 ) that demonstrated heritability of the metabolic storage lesion ( 21 23 ), as well as studies performed in mice ( 24 , 25 ) showing that post-transfusion recoveries are greatly variable across donors ( 26 ). Of note, Yoshida and colleagues have recently provided preliminary evidence suggesting that hemoglobin oxygen saturation (SO 2 ) at 8 h from donation and routine processing varies significantly across donors ( 27 ), potentially contributing to the donor-dependent development of the storage lesion.…”
Section: Introductionmentioning
confidence: 81%
“…Indeed, it has been documented that RBC units from a significant percentage of donors have 24‐hour recoveries of less than 75%, and for a small percentage of donors, 24‐hour recoveries are very poor (in the range of 20%‐30%) . The basis for donor‐to‐donor variability is poorly understood, but there is good evidence that it has a strong genetic component, at least at the metabolic level . Using tractable animal models of RBC storage, we have documented that both hemolysis and decreased 24‐hour recoveries vary in genetically distinct strains of inbred mice .…”
mentioning
confidence: 94%
“…2 The basis for donor-to-donor variability is poorly understood, but there is good evidence that it has a strong genetic component, at least at the metabolic level. [3][4][5][6][7] Using tractable animal models of RBC storage, we have documented that both hemolysis and decreased 24-hour recoveries vary in genetically distinct strains of inbred mice. 8,9 These strains serve as a platform to study basic mechanisms of variant RBC storage.…”
mentioning
confidence: 99%